Regional distribution and developmental expression of epidermal growth factor and transforming growth factor-alpha mRNA in mouse brain by a quantitative nuclease protection assay - Lazar, LM (J Neurosci, 1992)
A solution-hybridization ribonuclease-protection assay was used to identify epidermal growth factor (EGF) mRNA in mouse brain and to compare the regional and developmental levels of EGF gene expression in the CNS with those of its structural homolog, transforming growth factor-alpha (TGF-alpha). Adult brain regions examined included brainstem, cerebellum, cerebral cortex, hippocampus, basal hypothalamus, olfactory bulb, olfactory tubercle, striatum, and thalamus. While both EGF and TGF-alpha mRNAs were detected in all regions, TGF-alpha mRNA levels were 15–170 times higher, ranging from 0.39 (cerebellum and cerebral cortex) to 2.93 (striatum) pg TGF-alpha mRNA/micrograms total cytoplasmic RNA. In contrast, EGF mRNA levels ranged from 11 to 36 fg EGF mRNA/micrograms, with the highest regional concentrations observed in olfactory bulb, basal hypothalamus, and cerebellum. In our comparison between sexes, no significant male-female differences in EGF or TGF-alpha mRNA levels were observed for any region of adult brain. However, in the pituitary gland, consisting of both endocrine and neural elements, EGF and TGF-alpha mRNA levels were significantly higher in males (234 and 215 fg/micrograms, respectively) than in females (172 and 118 fg/micrograms, respectively). An examination of growth factor gene expression in the developing CNS revealed EGF and TGF-alpha mRNAs detectable as early as embryonic day 14 (earliest time point studied). While gene expression for both peptides continued into the postnatal period, EGF and TGF-alpha mRNA levels were nearly equal to adult concentrations by postnatal day 10. Taken together, our findings provide evidence for the synthesis of EGF in brain and suggest a role for both EGF and TGF-alpha in the development and support of the mammalian CNS.